2021
DOI: 10.1371/journal.pone.0259906
|View full text |Cite
|
Sign up to set email alerts
|

Levels and predictors of anxiety, depression, and stress during COVID-19 pandemic among frontline healthcare providers in Gurage zonal public hospitals, Southwest Ethiopia, 2020: A multicenter cross-sectional study

Abstract: Introduction The provision of quality health care during the COVID-19 pandemic depends largely on the health of health care providers. However, healthcare providers as the frontline caregivers dealing with infected patients, are more vulnerable to mental health problems. Despite this fact, there is scarce information regarding the mental health impact of COVID-19 among frontline health care providers in South-West Ethiopia. Objective This study aimed to determine the levels and predictors of anxiety, depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 69 publications
0
42
1
Order By: Relevance
“…Nurses with chronic medical illness, children to take care of at home, and rotational shifts contributed to increasing stress experiences (Dechasa et al, 2021;Baye et al, 2020). In the face of the current pandemic, depressive symptoms were high among nurses' secondary to the mental effects and concerns about safety (GebreEyesus et al, 2021;Yadeta et al, 2021). The findings of the current study had described the context of stress, anxiety, depression, and burnout in the workplace that serve to provide recommendations for needed action.…”
Section: Relationship Of Nurses' Stress Anxiety and Depression To Bur...mentioning
confidence: 79%
“…Nurses with chronic medical illness, children to take care of at home, and rotational shifts contributed to increasing stress experiences (Dechasa et al, 2021;Baye et al, 2020). In the face of the current pandemic, depressive symptoms were high among nurses' secondary to the mental effects and concerns about safety (GebreEyesus et al, 2021;Yadeta et al, 2021). The findings of the current study had described the context of stress, anxiety, depression, and burnout in the workplace that serve to provide recommendations for needed action.…”
Section: Relationship Of Nurses' Stress Anxiety and Depression To Bur...mentioning
confidence: 79%
“…A cross sectional study in Ethiopia showed similar results to our study with a prevalence of 20.2%, 21.9% and 15.5% for depression, anxiety and stress respectively [ 15 ]. Conversely, another study in Ethiopia had a slightly higher prevalence of stress of 31.4% while the prevalence of depression and anxiety were 25.8% and 36% respectively [ 16 ]. The incongruity of the results may be due to the use of different scales and different cut-off scores to measure depression, anxiety and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were categorized into normal, mild, moderate, severe and extremely severe according to the cut-off in the respective subscales. The depression subscale is made up of questions 3,5,10,13,16,17,21,24,26,31,34,37,38 and 42. This scale was divided into normal (0-9), mild depression (10-13), moderate depression (14-20), severe depression (21-27) and extremely severe depression (>28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations